(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
Microscale morphology in coastal environments is complex to study due to both the large spatial and temporal variability. No direct instrumentation is available to map the micromorphology in detail. The aim of this article is to describe the application of the newly developed MiSMoS (MicroScale Morphology System) methodology for mapping surface and small-scale morphologic features such as ripples, rills, and small courses, as well as to demonstrate its advantages and limitations. A set of measurements on a perched beach that offers varied microforms was carried out as a case study example. The MiSMoS consists of a table of 1.6 m x 1.6 m square aluminum structure with six L-shaped rails on top to mobilize a sensor-carrying structure, which is supported on 4 legs (0.60 m high). The sensor-carrying structure is built with two cameras and a Laser Distance Meter (LDM), with cameras at a fixed angle of 20°. In the operating procedure for high-resolution mapping, the sensor-carrying structure is manually moved sequentially capturing images that cover a surface of 0.60 x 0.60 m, with 75% overlap. High-resolution 3D models were generated from the images using Structure-from-Motion, Multi-View-Stereo (SfM-MVS) technique. MiSMoS has numerous advantages over commercial instrumentation: 1) it can map topography at a high resolution, 2) it is easy to build and deploy, 3) it is inexpensive, and 4) in one operation, a high-resolution map of an area of 2.25 m2 can be obtained in about 15-20 min, whereas other systems usually only provide profiles.